Efficacy and Safety of Astragalus-Containing Traditional Chinese Medicine Combined With Platinum-Based Chemotherapy in Advanced Gastric Cancer: A Systematic Review and Meta-Analysis - Cheng, Mengqi; Hu, Jiaqi; Zhao, Yuwei; Jiang, Juling; Qi, Runzhi; Chen, Shuntai; Li, Yaoyuan; Zheng, Honggang; Liu, Rui; Guo, Qiujun; Zhang, Xing; Qin, Yinggang; et al. (Frontiers in Oncology, 2021)
Background: Platinum-based chemotherapy (PBC) is one of the major treatments for advanced gastric cancer (AGC); however, it is associated with adverse reactions and chemotherapy resistance. Although Astragalus-containing traditional Chinese medicine (TCM) is widely used to treat AGC in China, evidence of its efficiency remains limited. This study aimed to evaluate the efficacy and safety of Astragalus-containing TCM combined with PBC in AGC treatment. Methods: We searched for literature (up to July 19, 2020) in the PubMed, EMBASE, Cochrane Central Register of Controlled Trials, Chinese Biomedical Literature database, Chinese Science and Technology Journals, Wanfang Database, and Chinese database of China National Knowledge Infrastructure. The included studies were reviewed by two researchers. Main outcomes were objective response rate (ORR), disease control rate (DCR), survival rate, quality of life (QOL), adverse drug reactions (ADRs), and peripheral blood lymphocyte levels. The effect estimate of interest was the risk ratio (RR) or mean difference (MD) with 95% confidence intervals (CIs). Results: This study included 35 randomized controlled trials involving 2670 patients. Compared with patients treated with PBC alone, those treated with Astragalus-containing TCM had better ORR (RR: 1.24, 95% CI: 1.15-1.34, P < 0.00001), DCR ( RR: 1.10, 95% CI: 1.06-1.14, P < 0.00001), 1-year survival rate (RR: 1.41, 95% CI: 1.09-1.82, P = 0.009), 2-year survival rate (RR: 3.13, 95% CI: 1.80-5.46, P < 0.0001), and QOL (RR: 2.03, 95% CI: 1.70-2.43, P < 0.00001 and MD: 12.39, 95% CI: 5.48-19.30, P = 0.0004); higher proportions of CD3+ T cells and CD3+ CD4+ T cells; higher ratio of CD4+/CD8+ T cells; nature killer cells; and lower incidence of ADRs. Subgroup analysis showed that oral and injection administration of Astragalus-containing TCM both increased tumor response. Whether treatment duration was ≥ 8 weeks or  8 weeks, Astragalus-containing TCM could increase tumor response in AGC patients. Furthermore, Astragalus-containing TCM combined with oxaliplatin-based chemotherapy could increase ORR and DCR, while when with cisplatin, it could only increase ORR. Conclusion: The results indicated that Astragalus-containing TCM combined with PBC had better efficacy and less side effects in the treatment of AGC, but more high-quality randomized studies are warranted.